PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN KUALITAS INTEGRATED REPORTING SEBAGAI VARIABEL INTERVENING - Yannes Manurung (PT Sanagi Edu Konsultan, 2025)
This study aims to examine the effect of good corporate governance on financial performance with the quality of integrated reporting as an intervening variable. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX. This research uses quantitative methods with secondary data. Data for financial performance variables are taken from datastream, while data for integrated reporting quality variables are taken from the company's annual report accessed through www.idx.co.id and the company's official website respectively. Data analysis and hypothesis testing in this study were carried out by multiple linear regression and path analysis with the help of SPSS 23 software. The results of this study indicate that the audit committee, institutional ownership, managerial ownership, and board of commissioners structure have no significant effect on financial performance, good corporate governance has a significant effect on the quality of integrated reporting and good corporate governance has no significant effect on financial performance through the quality of integrated reporting.